2019
DOI: 10.1136/bmjopen-2019-029784
|View full text |Cite
|
Sign up to set email alerts
|

Cohort profile: the Canadian coordination and activity tracking in children (CATCH) longitudinal cohort

Abstract: PurposeDevelopmental coordination disorder (DCD) is a prevalent, neurodevelopmental disorder affecting 2% to 5% of children, which is characterised by fine and gross motor problems. Children with DCD have been shown to be less fit and physically active than other children; however, the direction of causality is unknown as previous studies have typically been done in older children when the differences in fitness and physical activity are already present. The aim of the Coordination and Activity Tracking in Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…The two groups of participants in each experiment were not statistically different in age, IQ, or digit span working memory index (WMI; Wechsler Intelligence Scale for Children, 4 th ed., Wechsler, 2003; see Table S1). Note that we do not argue that rDCD and TD children have equivalent IQ; indeed studies with larger sample sizes have shown significant differences (e.g., IQ 106.1 vs. 100.9, or percentile 65.6 vs. 52.4; Cairney et al, 2019). Nevertheless, whether IQ differs between groups was not the main interest of the current study and, importantly, our statistical models showed that IQ did not associate with behavioral thresholds or ERP effects, suggesting that IQ is unlikely to be a confounding factor for our conclusions (see Comparing age, working memory and IQ between groups in Supporting Information).…”
Section: Participantsmentioning
confidence: 54%
See 1 more Smart Citation
“…The two groups of participants in each experiment were not statistically different in age, IQ, or digit span working memory index (WMI; Wechsler Intelligence Scale for Children, 4 th ed., Wechsler, 2003; see Table S1). Note that we do not argue that rDCD and TD children have equivalent IQ; indeed studies with larger sample sizes have shown significant differences (e.g., IQ 106.1 vs. 100.9, or percentile 65.6 vs. 52.4; Cairney et al, 2019). Nevertheless, whether IQ differs between groups was not the main interest of the current study and, importantly, our statistical models showed that IQ did not associate with behavioral thresholds or ERP effects, suggesting that IQ is unlikely to be a confounding factor for our conclusions (see Comparing age, working memory and IQ between groups in Supporting Information).…”
Section: Participantsmentioning
confidence: 54%
“…Note that criterion (b) was not directly applied in the current study because we were concerned that the difficulties in activities of daily living may not be very apparent during the early years (Cairney et al, 2019), and questionnaires to assess the impact of DCD on everyday activities have not yet been validated for this age (Cairney et al, 2015). These assessments were done in an additional session as part of the CATCH study (Cairney et al, 2015(Cairney et al, , 2019. It should be noted that participants did not receive a formal medical diagnosis of DCD from a pediatrician or physician.…”
Section: Defining Cases Of Rdcd and Tdmentioning
confidence: 99%
“…The CATCH cohort contains 589 children (please see Cairney et al (24) for further details of the full cohort). Seven children (1.2%) had missing or incomplete data on the CBCL and were excluded from the present analysis, leaving 582 participants.…”
Section: Resultsmentioning
confidence: 99%
“…A higher-than-expected probability of motor impairment also necessitated changes to the randomization probabilities and processes to maintain approximate group balance. The screening and recruitment process is described more fully elsewhere (24). Ethical approval was obtained from the Hamilton Integrated Research Ethics Board at McMaster University.…”
Section: Methodsmentioning
confidence: 99%
“…Childhood is a very favourable time to develop motor skills and physical fitness, but most recent studies show that motor skills and physical fitness are declining in many countries (Luz et al, 2019). Poor physical fitness and physical inactivity are responsible for poorer motor system coordination as such children are physically weaker and less active (Cairney et al, 2019). Recent research results show that physical fitness has a positive effect on children's academic achievements in math, arts, science and social sciences.…”
Section: Introductionmentioning
confidence: 99%